2020
DOI: 10.3389/fnut.2020.00023
|View full text |Cite
|
Sign up to set email alerts
|

Protein Deficiency-Induced Behavioral Abnormalities and Neurotransmitter Loss in Aged Mice Are Ameliorated by Essential Amino Acids

Abstract: Nutritional epidemiology shows that insufficient protein intake is related to senile dementia. The levels of protein intake in aged people are positively associated with memory function, and elderly people with high protein intake have a low risk of mild cognitive impairment. Although the beneficial roles of protein nutrition in maintaining brain function in aged people are well demonstrated, little is known about the mechanism by which dietary intake of protein affects memory and brain conditions. We fed aged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 38 publications
(42 reference statements)
4
40
0
Order By: Relevance
“…It is not possible to elucidate the mechanism based solely on the results of this study, which aimed to investigate the intervention effect of essential amino acid intake. Our initial hypothesis regarding this composition, Amino LP7 ( 8 ), was based on the amino acid influx rate to the brain, which would reflect the requirement for each amino acid to maintain brain homeostasis against neurodegenerative processes; we composed a mixture of seven essential amino acids rich in leucine, phenylalanine, and lysine to directly match the ratios associated with the brain influx rate. It is possible that Amino LP7 acts via multiple mechanisms, including neurotransmitter compensation ( 8 ) and competitive inhibition of neurotoxic substance influx into the brain.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is not possible to elucidate the mechanism based solely on the results of this study, which aimed to investigate the intervention effect of essential amino acid intake. Our initial hypothesis regarding this composition, Amino LP7 ( 8 ), was based on the amino acid influx rate to the brain, which would reflect the requirement for each amino acid to maintain brain homeostasis against neurodegenerative processes; we composed a mixture of seven essential amino acids rich in leucine, phenylalanine, and lysine to directly match the ratios associated with the brain influx rate. It is possible that Amino LP7 acts via multiple mechanisms, including neurotransmitter compensation ( 8 ) and competitive inhibition of neurotoxic substance influx into the brain.…”
Section: Discussionmentioning
confidence: 99%
“…Our initial hypothesis regarding this composition, Amino LP7 ( 8 ), was based on the amino acid influx rate to the brain, which would reflect the requirement for each amino acid to maintain brain homeostasis against neurodegenerative processes; we composed a mixture of seven essential amino acids rich in leucine, phenylalanine, and lysine to directly match the ratios associated with the brain influx rate. It is possible that Amino LP7 acts via multiple mechanisms, including neurotransmitter compensation ( 8 ) and competitive inhibition of neurotoxic substance influx into the brain. As the constituents of Amino LP7 have high rates of influx into the brain via specific transporters (e.g., LAT-1), it is plausible that Amino LP7 not only delivers the neurotransmitter substrate into the brain but also competitively inhibits the blood-to-brain transfer of toxic amino acid metabolites, such as kynurenine, that share the same transporters ( 38 , 39 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies that experimentally increased brain noradrenaline noted improved attention in rats (Sirviö et al 1993) and maze solving performance in mice (Avraham et al 1996). Moreover, study on aged mice showed that oral administration of seven essential amino acids (precursors of neurotransmitters) to low-protein diet mice reversed behaviour abnormalities related to learning and memory impairment (Sato et al 2020).…”
Section: Discussionmentioning
confidence: 99%